Correlation between ankle stiffness and antagonist co-activation in post-stroke subjects - Ribeiro, Edgar (2021)
Tonus dysfunction has been broadly investigated in post-stroke subjects through the evaluation of muscle resistance against stretching, however, its characterisation in functional context is challenging. This study aims to analyse the correlation between intrinsic stiffness, functional stiffness and antagonist co-activation at the ankle joint of post-stroke subjects. Both lower limbs of eight post-stroke participants were evaluated. Intrinsic stiffness was assessed during passive dorsiflexion by an isokinetic dynamometer, functional stiffness during upright standing on a force platform and antagonist co-activation was obtained in upright standing and postural phases of gait initiation and stand-to-sit through the electromyographic signal of ankle muscles.